2001
DOI: 10.1242/jeb.204.16.2781
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations of the Transepithelial Potential of Moth Olfactory Sensilla Are Influenced by Octopamine and Serotonin

Abstract: SUMMARY The biogenic amine octopamine is known to enhance the sensitivity of male moths to their species-specific pheromones in flight-tunnel experiments. This sensitization of pheromone-guided upwind flight is at least partly due to octopamine-dependent increases in the peak nerve impulse frequency of the pheromone response of olfactory receptor neurons. It is not known, however,whether octopamine exerts its effects directly on the electrical properties of the olfactory receptor neurons or indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…By measuring the responses of ORNs after suppressing the expression of corresponding genes, we demonstrated that the Lmig5-HT 2 receptor plays an inhibitory role in the response of ORNs to odorants, which results in the regulation of the signal output. Previous studies in moths suggested that 5-HT 2 in the sensillum, lymph might regulate neuronal activity by altering the transepithelial potential, thus changing the threshold of firing without influencing the spontaneous action potential activity of ORNs (Dolzer et al, 2001). Because ORNs performed in very similar patterns when locusts had knockdown of GABA b , we suggest that regulation by the Lmig5-HT 2 receptor may indirectly Our findings indicate that the depression of the 5-HT 2 and GABA b receptors increased sensory responses to odors, and in other words, the 5-HT 2 and GABA b attenuated sensory response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By measuring the responses of ORNs after suppressing the expression of corresponding genes, we demonstrated that the Lmig5-HT 2 receptor plays an inhibitory role in the response of ORNs to odorants, which results in the regulation of the signal output. Previous studies in moths suggested that 5-HT 2 in the sensillum, lymph might regulate neuronal activity by altering the transepithelial potential, thus changing the threshold of firing without influencing the spontaneous action potential activity of ORNs (Dolzer et al, 2001). Because ORNs performed in very similar patterns when locusts had knockdown of GABA b , we suggest that regulation by the Lmig5-HT 2 receptor may indirectly Our findings indicate that the depression of the 5-HT 2 and GABA b receptors increased sensory responses to odors, and in other words, the 5-HT 2 and GABA b attenuated sensory response.…”
Section: Discussionmentioning
confidence: 99%
“…The odorants pass through the pores on the sensillar wall and are then bound by OBPs that are secreted by accessory cells to form the odorant/OBP complex, which is transported onto ORs and OR co-receptors on the membranes of ORN dendrites, thus evoking action potentials in ORNs (Laughlin et al, 2008). Studies have shown that in the antennae of male Manduca sexta moths, 5-HT affects the transepithelial potential, generated by accessory cells in the olfactory sensillum and creates a driving force for the receptor current (Dolzer et al, 2001;Grosmaitre et al, 2001), whereas it has no direct effect on the activity of spontaneous action potential of olfactory receptor neurons (Dolzer et al, 2001). This is consistent with our results that the 5-HT receptor is expressed in the accessory cells but not on ORNs, which suggests that 5-HT acts directly on accessory cells to affect the ORNs when acting in the peripheral nervous system, rather than directly on ORNs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spontaneous spike activity recorded from each of the TAG nerves N4 to N6 was analysed by means of the Clampfit 10.0 software (Axon Instruments) [ 42 , 43 , 44 ]. Spikes in the discharges were sorted out by a threshold-based search and then their peak-to-peak amplitude (PPA) and the max decay slope (MDS) of each spike were measured as an index of their amplitude and shape, respectively, and plotted versus the time of occurrence.…”
Section: Methodsmentioning
confidence: 99%
“…An example of non-associative learning is adaptation of olfactory sensory neurons. Olfactory adaptation employs, e.g., Ca 2+ -dependent negative feedback control mechanisms to prevent damage via overstimulation after a very strong or long odor/pheromone stimulus ( Zufall and Leinders-Zufall, 2000 ; Dolzer et al, 2001 ; Spehr et al, 2009 ; Stengl, 2010 ). Hebbian plasticity mechanisms shift the current physiological dynamic setpoint to a new dynamic setpoint, for example, measurable as shifted dose-response curve of the sensory neurons.…”
Section: Introductionmentioning
confidence: 99%